The Popular Image of the Young Generation on Social Media: (A Comparative Study of Jerome Polin and Vina Mauliana's Self-Branding on Instagram) - Adrianda, Irsan (Jurnal Ilmiah Teunuleh, 2025)
This study aims to examine how two figures of the Young Generation, namely Jerome Polin and Vina Mauliana, represent themselves and build personal branding through Instagram. Using a document study approach and critical discourse analysis of some uploaded content in 2023 to 2024, this study explores how both build digital identities as popular figures. Referring to  Erving Goffman's self-presentation theory  , Stuart Hall's concept of representation, as well as the personal branding framework, it was found that the two figures use social media not only to share knowledge and motivation, but also to build a public persona that is inspiring, professional, and easily accepted by the wider community. The results of the analysis show that Jerome displays a productive and global intellectual image with an educational-entertainment communication style, while Vina represents a reflective and spiritual image with an emotional and personal narrative approach. The comparison of representation strategies shows that the younger generation is able to build  a diverse but consistent self-branding through social media, depending on the personal values they highlight. These findings confirm that digital identity in the age of social media is not a fixed entity, but rather a symbolic construct that is consciously formed in online visual and verbal interactions.